Investigating employer perspectives on the polytechnic sector's industrial training program: A case study of iranian companies - Abareshi, Mohammad (Annals of Management and Organization Research, 2025)
Purpose: Industrial training programs are structured educational initiatives that provide supervised, practical experience within designated timeframes in both the private and government sectors. The primary objective was to bridge the gap between theoretical knowledge and practical skills, allowing participants to apply classroom learning in real-world environments. This hands-on approach enhances competency development, understanding of industry practices, teamwork, and professional ethics, ultimately preparing individuals for successful careers in various industries. Research Methodology: Data analysis was performed using a specialized statistical software tool designed for predictive modeling and analysis. This tool was employed to examine and interpret the dataset, thus enabling the extraction of meaningful insights and predictions. The analytical process involves a series of statistical techniques, algorithms, and models to identify patterns, correlations, and trends within the data. By leveraging the capabilities of this advanced statistical package, the research team derived valuable information, made informed predictions, and drew significant conclusions from comprehensive data analysis. Results: From the instructors' perspective, industrial training significantly enhances students' proficiency in both formal and informal communication, assists them in identifying appropriate research areas for their projects, and improves their socialization and relationship-building skills. Employees reported that industrial training increased their confidence in problem solving and emphasized the importance of continuous learning. A notable challenge faced by employees during their internships is related to workplace safety. Limitations: The findings of this study are primarily applicable in educational settings. Contribution: Our study concludes that industrial training is crucial for enhancing students’ post-training abilities and knowledge. We recommend recognizing industrial training as an essential tool for improving employees' skills and capabilities.